RICE YIELD IMPROVEMENT THROUGH VARIOUS DIRECT SEEDING TECHNIQUES ON MODERATELY SALT AFFECTED SOIL - M. Jamil1; S. S. Hussain; M. A. Qureshi3; S. M. Mehdi; M.Q. Nawaz; Q. Javed (Journal of Animal and Plant Sciences, 2017)
Rice is usually cultivated under flooded conditions by transplanting, an expensive, time consuming and required significant labour pool as compared to the direct seeded rice. Canal water is not satisfying the required demand and ground water at most of the places is unfit for irrigation except some patches. Under prevailing conditions, direct seeded rice is the ultimate strategy for optimum production of rice. Assessment of the different sowing techniques viz. broadcast, ridge and drill sowing and different fertilizer rates on the paddy yield on moderately salt affect soil was executed through field experiments at Research Farm of Soil Salinity Research Institute, Pindi Bhattian, district Hafizabad, Punjab during 2010-2012. Three methods of sowing i.e. ridge, drill and broadcast sowing and five N levels viz. T1: farmer practices (80-60-0 NPK kg ha-1), T2: Recommended dose (RD) (110-90-60 NPK kg ha-1), T3: 75% N of RD, T4: 125% N of RD and T5:150% N of RD.Trial was laid out in split plot arrangement with three replications. Results revealed the better growth and development, yield attributes and ultimately the highest paddy yield (4.46 t ha-1) at 150% N of recommended dose fromridge sowing followed by 125% N of recommended dose with 4.35 t ha-1 production. Among the sowing techniques, ridge sowing proved the best with all growth, development and yield parameters at the optimum followed by drill sowing. Studies concluded that the effect of various sowing techniques, N rates and their interaction was significant on yield components of direct seeded rice. Nitrogen rate @ 150 % N of RD gave the maximum yield which was statistically at par with the 125% N of RD. Among sowing techniques, ridge sowing proved superior followed than drill and broad cast sowing.Slight decrease in ECe and SAR was observed with drill sowing at higher rates of N i.e. 125 and 150% of RD.
Keywords: Direct seed rice; nitrogen rates; sowing methods; paddy yield; Salt affected soil; Rice